Ending Inflation in the People's Republic of China: From Chairman Mao to the 21st Century - Richard C.K. Burdekin (Claremont McKenna College, Department of Economics, 2000)
In the post-1978 reform period the People's Republic of China experienced its most serious open inflationary problems since 1949-1950. This paper compares the 1949-1950 case to more recent Chinese attempts at inflation control and considers the role played by budget deficits, indexation and direct intervention in commodity markets. While inflationary problems subsided by the mid-1990s, continuing deficit-spending pressures and weaknesses in China's banking system still pose a very real danger. The financial reforms undertaken in the late 1990s include initiatives directed at the bad debts accumulated in China's banks by loss-making state enterprises.
Keywords: 330